Eight Khalkha Jebtsun-damba Khutukhtu and Pandito Khambo-Lama Dashi-Dorzho Itigelov, 1911–1915 - Leonid V. Kuras; Bazar D. Tsybenov (Oriental Studies)
Introduction. In 2024, Mongolia shall celebrate the 155th birthday of the Eighth Bogdo Gegeen — the political figure who founded modern Mongolian statehood in the early twentieth century. This charismatic leader was the one who took both secular and religious power over the new Mongolia. The article introduces into scientific circulation a variety of documents from the State Archive of Buryatia that show the actual attitudes of Imperial Russia’s Buddhists — articulated by the Twelfth Pandito Khambo-Lama — to the restoration of Mongolian statehood, and their reverence to the inspirer of the Mongolian Revolution. The examined official correspondence between Khambo Lama of ethnic Buryatia D.-D. Itigelov and Governor-General of Transbaikalia A. I. Kiyashko reveal a number of issues pertaining to the interaction between the spiritual leaders of Mongolia and Russia, show the actual attitude of Russia’s officials toward the Mongol statehood’s restoration, this very attitude to become, in fact, a political guarantee for the very existence of that statehood. Goals. The study attempts an insight into the official 1911–1913 correspondence between Pandito Khambo-Lama and Russian/Mongolian regional officials. To facilitate this, the paper shall analyze the correspondence between Pandito Khambo-Lama and Governor-General of Transbaikalia (December 1911 – February 1912); examine the former’s correspondence with Russian and Mongolian authorities (December 1912 – January 1913); investigate his letters discussing a dispatch of a special delegation comprising Buryat clerics and officials to Urga (April–May 1913). Conclusions. The study attests to Buryat Buddhists in the face of Pandito Khambo-Lama of Eastern Siberia D.-D. Itigelov sincerely welcomed the newly established Mongolian Government headed by the Eighth Bogdo Gegeen. The official correspondence between the spiritual leader of R ussian Buddhists and regional, Mongolian authorities shows both Imperial Russia’s cautious policy in the Mongolian question, and the bureaucratic slowness. Buryat Buddhists led by Pandito Khambo-Lama D.-D. Itigelov succeeded in arranging a special delegation to Urga to congratulate the Eighth Bogdo Gegeen and Mongolian people upon the declared independence of theirs.